Community Political Participation in the Development of a Participatory Supervision Program by the Citizens' Forum of BAWASLU ( The General Election Supervisory Agency) Takalar Regency in the General Elections 2019 - Sufirman Sufirman; Andi Surahman Batara (Universitas Islam Darul Ulum Lamongan, 2023)
This study aims to find out how the involvement of civil society (Civil Society) in the participatory surveillance of the 2019 General Elections in the South Sulawesi Province is specific in the Takalar district. Another goal is to find facts thanks to the development and implementation of participatory surveillance models and forms of civil society involvement in the 2019 general election in Takalar district. This research is qualitative research with a descriptive case study approach. Data in this study uses primary data and secondary data. Data is collected through several methods such as observations, interviews, and library studies. The results of the research showed that this research concluded the development process of the participatory surveillance program through the involvement of the civil society in the Bawaslu district of Takalar from the 7 (seven) dominant participatory monitoring programs through the formation of the Election Awakening Forum which then networked to form the village/environment or village of the election surveiller through three stages, namely a) the stage of socialization; b) the formation stage and c) the development stage, the three processes are implemented in the Bavaslu District of takalar as an effort to enhance the participation of the community involved in performing surveys. At the stage of development of the Model of Participatory Surveillance implemented by making the pilot project of the Village Aware Election and Anti-Political Money in the Village Massamaturu district of Takalar, through the Government of the Municipality of the village Aware Forum of the People's Party and Anti Political Money is estimated through the Village Fund Anggran with the Nomenclature of Socialization and Legal Protection for the community This Program is submitted to the Forum Aware to be further managed and focus on socialization and protection of the community related to the rules and the Election Law. Another finding from the results of this study is that the participatory surveillance development program of Bawaslu is oriented on Prevention through socialization and political-democratic education to society for the realization of integrated and dignified elections.